2014
DOI: 10.3233/jad-141203
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Brain Hypoperfusion due to Multi-Vessel Extracranial Atherosclerotic Disease: A Potentially Reversible Cause of Cognitive Impairment

Abstract: A 62-year-old patient presented with persistent cognitive deficits 3 months after a right temporal ischemic stroke due to ipsilateral carotid occlusion. Work-up disclosed hemodynamically significant contralateral carotid artery stenosis and left subclavian steal phenomenon. Brain SPECT imaging revealed bihemispheric chronic brain hypoperfusion that substantially improved on repeat imaging when the subclavian steal was temporarily diminished by inflating a cuff around the left arm. Carotid endarterectomy of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…A recent case report described a patient with left SSS and bilateral carotid artery atherosclerosis presenting with cognitive impairment from chronic cerebral hypoperfusion. The patient exhibited significant cognitive improvement after surgical treatment …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent case report described a patient with left SSS and bilateral carotid artery atherosclerosis presenting with cognitive impairment from chronic cerebral hypoperfusion. The patient exhibited significant cognitive improvement after surgical treatment …”
Section: Introductionmentioning
confidence: 99%
“…The patient exhibited significant cognitive improvement after surgical treatment. 23 Clinical suspicion is important for the diagnosis of SSS because symptoms are often atypical and most cases are asymptomatic. However, the attribution of symptoms to a proven SSS must be made with caution, and only after exclusion of other causes such as orthostatic hypotension, cerebellar lesions, vestibular malfunction, cardiac disease, brachial plexus pathology, and thoracic outlet syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Rocque et al reported that patients with large carotid plaques are more likely to have cognitive impairment ( 54 ). Pathophysiologically, multi-vessel, extracranial atherosclerotic disease may cause chronic diffuse brain hypoperfusion, which may be associated with cognitive impairment ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…CCCI, which was initially proposed by Japanese scholars in the 1990s, refers to a state of reduction in cerebral blood flow (CBF) below the physiologically required volume, leading to brain dysfunctions, and this state should, more often than not, last for at least 2 months. CCCI can be secondary to a variety of etiologies, with atherosclerosis predominating …”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have revealed that the symptoms of CCCI, such as dizziness and headache, are actually reversible once cerebral circulation is improved . On the contrary, persistent CBF reduction, if not corrected, may evoke stroke, TIA, vascular cognitive impairment, or even dementia . Therefore, identifying this condition followed by prompt and effective intervention is enormously valuable.…”
Section: Introductionmentioning
confidence: 99%